Transradial access chemoembolization for hepatocellular carcinoma in comparation with transfemoral access - Du, Nan; Yang, Min-Jie; Ma, Jing-Qin; Luo, Jian-Jun; Zhang, Zi-Han; Yu, Tian-Zhu; Zheng, Zhi-Yuan; Zhang, Wen; Yan, Zhi-Ping (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study aimed to compare the safety and efficacy of transradial access (TRA) with transfemoral access (TFA) chemoembolization in treatment of hepatocellular carcinoma (HCC). Methods: HCC patients who were late for curative treatment on initial diagnosis or HCC patients who had undergone one or several rounds of transarterial chemoembolization (TACE) were enrolled. The clinical and angiographic characteristics, the procedure related details, and the follow-up data from patients who underwent TRA and TFA were analyzed and compared. Results: In total, 112 patients undergoing 160 TRA-TACE and 107 patients undergoing 163 TFA-TACE were included. The technical success rate of TRA was 95.0% and that of TFA was 98.8% (P=0.102). In the TFA-TACE group, 5.5% of cases suffered access site-related complications, including 6 with minor bleeding and 3 with severe bleeding or pseudoaneurysm. In the TRA-TACE group, 1.9% of cases underwent crossover to femoral access for selective cannulation failure. The rate of radial artery occlusion (RAO) was 2.7% (3 of 112 patients), and none of the RAO patients suffered paresthesia, pain at the site of occlusion, hand function loss or distal ischemia. Comparing patients with/without access site-related complications in the TFA-TACE group, there was a statistical difference in patient age and in the percentage of patient with a PT time >15 s (72.6% vs. 57.1%, P